Brass Bands of the Lithuanian Emigrants in the USA and the National Movement - Žarskienė, Rūta (Tautosakos darbai, 2020)
The subject of the article is the brass bands organized by the first wave of the Lithuanian emigrants to the USA and their activities. Employing the historiographic method, the author aims at revealing how organizing the bands and participating in their activities contributed to enhancing the Lithuanian national consciousness and spread of the Lithuanian culture. The majority of Lithuanians arriving to the USA in the end of the 19th – beginning of the 20th century consisted of semiliterate peasants that mostly settled in Pennsylvanian towns, in Chicago and New York, laboring hard in the coal mines, butcheries, and factories. Earlier American settlers of the West European origins were not too friendly to the new arrivals from the Eastern and Southern Europe, therefore those arriving in the end of the 19th – beginning of the 20th century had to find ways of establishing themselves in the spheres of religion and culture. Thus, the immigrant Lithuanians used to gather together, organize parishes, build churches, create Lithuanian schools and musical groups, and publish periodicals. Lithuanians quickly realized that brass band activities could bring them closer to the other, more educated and culturally advanced national communities of the USA, and therefore tried to establish the bands in all their colonies or at every bigger society. Usually, these bands consisted of miners and other workers with no musical education, who could not read notes or play any wind instrument before joining a band. The societies would purchase the instruments and hire the band leaders. Some bands would play “by ear” and perform only to their close associates. Others, consisting of better, more educated players, could reach a considerably high level of performance, and represented not only their society or town, but also could participate in public events, and got invitations from other national communities. The chief activities of these bands included marching along the streets during festivities organized by the Lithuanians or by the town municipality. Their music announced the event that was taking place, enhanced its celebratory character, attracted the passersby’ attention and boosted the mood of its participants. Thus, Lithuanians settled in America and seeking to establish their identity used to be proud of their Lithuanian brass bands. When performing the repertoire that differed from that of other national groups living in the USA (e.g. Germans, Irish, Italians or African Americans) they would express their Lithuanian identity and nationality, and promote the name of Lithuania in the multicultural environment of the United States. Approximately, from the 1910s or 1920s, the brass bands were increasingly replaced by ensembles combined of wind and string instruments performing dance music during smaller festive events of the Lithuanian communities. Smarter Lithuanian performers, having learned to play some instrument at the brass band, would organize smaller ensembles and earn a living by playing at saloons, weddings, or balls. The popularity of such ensembles that would frequently use similar names to the brass bands is evident from the vinyl sound recordings published in America in the second quarter of the 20th century. However, after the Second World War, the tradition of the Lithuanian brass bands virtually died out in the USA. The second wave of the Lithuanian emigrants, having been raised in the interwar Lithuania in the national spirit, used other means of expressing their national identity, and the brass instruments were replaced by kanklės (Lithuanian zither), birbynės (reed pipes), skudučiai (multi-pipe whistles), and other ethnic folk music instruments.